Efisiensi penggunaan tiny oil pada saat start up boiler PLTU pacitan - Wawan Trisnadi Putra; Muh. Malyadi; Moch. Sofyan Anas (Jurnal Teknik Mesin Indonesia, 2016)
On the boiler combustion technique using tiny oil gun is a new environmentally friendly technologies. Application of tiny oil gun on the boiler pulverized coal can reduce oil consumption HSD, ensuring combustion stability at low load conditions and prevent loss of heat energy in the combustion chamber. The tiny oil burner technology used in the sub-critical pulverized coal boiler Pacitan power plant 315 MW. The purpose of this study was to determine the performance and combustion characteristics of a tiny oil gun and compare the efficiency of the use of tiny oil gun at startup conditions in Pacitan 315 MW power plant boiler when compared to using the oil gun. From the analysis of the operating data can be known the performance results of the tiny oil gun is farmore efficient than oil gun, which reached 74.8%.